Rectovaginal Fistula With Double Vagina and Anastomotic Stenosis: A Case Report Following Rectal Cancer Surgery - Li, Qiwei; Sun, Jianhua; Yin, Lu; Ji, Fu (Frontiers in Oncology, 2021)
Rectovaginal fistula (RVF) occurs as a result of abnormal epithelialized connections between the rectum and vagina. Rectal cancer surgery remains the major cause of RVF. Here, we report a rare postoperative complication in which a patient with a double uterine and vagina received RVF following rectal cancer surgery. The patient received radiotherapy and developed rectal anastomotic stenosis leading to scar hyperplasia around the fistula, making repair difficult. Complex RVF is prone to release, which despite the multitude of procedures and treatments reported, optimal strategies remain controversial. Our previous studies showed how the use of rectal mucosal advancement flap (RMAF) with transanal endoscopic surgery (TES) can repair mid-low RVF. We successfully repaired RVF and rectal anastomotic stenosis with staging TES in this complex case. This highlights the safety and utility of TES treatment for complex RVF. Further studies are now required to confirm its effectiveness.